Computational Prediction of Hot Spots and Binding Site of Inhibitor NSC23766 on Rac1 Binding With Tiam1 - Zheng, Chunwen; Wu, Xiaodong; Zeng, Ruijie; Lin, Lirui; Xu, Liyan; Li, Enmin; Dong, Geng (Frontiers in Chemistry, 2021)
Rac1 is a small signaling protein, which belongs to the Rho subfamily of Ras superfamily. It is activated by binding GTP and inactivated by exchanging GDP for GTP. The ability of nucleotide exchange depends on guanine nucleotide exchange factors (GEFs) family proteins. T-lymphoma invasion and metastasis factor 1 (Tiam1) is a member of GEFs. Rac1 participates in multiple signaling pathways and regulates various cellular events by interacting with GEFs. Particularly, it is involved in the development and progression of various kinds of tumors. In this paper, we studied the detailed interaction between Rac1 and Tiam1. Seven residues on Rac1 are predicted to be important for the interaction with Tiam1, i.e. E31, Y32, D38, N39, Y64, D65 and W56. All these residues are located on the switch 1 and 2 domains which are the interface between Rac1 and Tiam1, except W56. In addition, we analyzed how the inhibitor NSC23766 interacts with Rac1-Tiam1 complex. Our docking results show that the NSC23766 binding to the region belongs to switch 1 and 2 domains. Thus, the hot spots for NSC23766 binding are similar with those in Rac1-Tiam1 complex. These findings are very useful for the structure-based design of inhibitors toward Rac1.